Penerimaan Diri Orang dengan HIV/AIDS: Literature Review - Putu Winadia Audina; David Hizkia Tobing (Humanitas (Jurnal Psikologi), 2023)
HIV/AIDS is one of the deadliest diseases worldwide, including. According to Ethel (2016), HIV/AIDS causes many negative impacts, especially for infected individuals. Besides the decline in health aspects, PLWHA tend to get negative stigma and discrimination from the surrounding community. All those stigma and discrimination will indirectly add to the psychological burden which will eventually result in their difficulty in accepting their situation. Self-acceptance is a person's ability to accept themself, which is related to psychologically healthy conditions, having awareness, and full acceptance of who and what they are (Sari, 2018). Individuals who are able to accept themselves mean that individuals are also able to understand themselves, adjust to their environment, and are not afraid to look at themselves honestly. This paper is made to conduct a literature review of studies related to self-acceptance in people with HIV/AIDS. The descriptive literature review was conducted on 8 qualitative studies with varied sampling methods. The results of the literature review show that people with HIV/AIDS from various backgrounds have a fairly positive self-acceptance. This self-acceptance is described in various forms by each PLWHA. In addition, the phases that each PLWHA goes through and the supporting factors, as well as obstacles for PLWHA in accepting themselves are also quite diverse.